2013
DOI: 10.1007/s10661-013-3064-z
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal content in oysters (Crassostrea gigas) cultured in the Ebro Delta in Catalonia, Spain

Abstract: The aim of this study was to determine heavy metal content (As, Cd, Cu, Hg, Cd, Pb, and Zn) in oysters transplanted in Ebro Delta bays (Alfacs and Fangar) where oysters are traditionally cultured for human consumption. Metal body burdens were monitored weekly during the period of maximal agriculture activity from May to June in 2008 and 2009. Results indicate that regardless of the high levels of metals reported in biota living in Ebro River, metal levels in oysters from both bays were similar to those found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 49 publications
2
5
1
Order By: Relevance
“…Compared to Zn, the concentration of Cu was one order of magnitude lower. The large ratio between Zn and Cu was in agreement with previous reports that accumulation of Zn and Cu represents an antagonistic effect in many marine invertebrates, such as oyster (Ochoa et al 2013), mussel (Wang et al 2005), Sea Urchin , and also sea cucumber (Xing and Chia 1997). In addition, it is worth noting that As levels was higher than the essential metals Cu and Cr, which suggest that As tends to accumulate in A. japonicus.…”
Section: Resultssupporting
confidence: 91%
“…Compared to Zn, the concentration of Cu was one order of magnitude lower. The large ratio between Zn and Cu was in agreement with previous reports that accumulation of Zn and Cu represents an antagonistic effect in many marine invertebrates, such as oyster (Ochoa et al 2013), mussel (Wang et al 2005), Sea Urchin , and also sea cucumber (Xing and Chia 1997). In addition, it is worth noting that As levels was higher than the essential metals Cu and Cr, which suggest that As tends to accumulate in A. japonicus.…”
Section: Resultssupporting
confidence: 91%
“…The concentration of heavy metals in oyster tissues at the end of the study was below the limits of various norms, among them, the rules of the European Union, Australian and New Zealand legislation on Heavy metals in food, Brazilian legislation on heavy metal (Díaz, 2019) andFDA (2012). The observed values, in general, were lower than those found in C. gigas cultivated in Korea (Mok et al, 2015), Spain (Ochoa, Barata, & Riva, 2013) and Mexico (Góngora et al, 2017).…”
Section: Discussioncontrasting
confidence: 71%
“…In this study, the ranking of metal concentrations in C. gigas reflects the typical metal accumulation of other Crassostrea species (Phillips & Muttarasin, 1985;Páez-Osuna & Marmolejo-Rivas, 1990a;Lin & Hsien, 1999), for which Zn posted the highest level and Hg the lowest. Osuna-Martínez et al (2010) and Ochoa et al (2013) highlighted the importance of oyster depuration prior to being analyzed for heavy metal concentration in order to eliminate digested and undigested food and other particles from gut contents with a potentially high-trace metal burden. This procedure allows us to quantify metal accumulation in body tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Lyle-Fritch et al (2006) identified 106 different types of products, and approximately 42 products that are commonly applied at shrimp farms. As, essential element for normal growth and development (Ochoa et al, 2013), Cu is present in aquatic invertebrates and its bioaccumulation can increase with size (Pan & Wang, 2009). The consumption of oysters with high Cu levels can cause irritation, vomiting, and ulcer and kidney damage (ATSDR, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation